Archetypes and Controls of Riverine Nutrient Export Across German Catchments. Issue 4 (26th April 2021) - Ebeling, Pia; Kumar, Rohini; Weber, Michael; Knoll, Lukas; Fleckenstein, Jan H.; Musolff, Andreas
Abstract: Elevated nutrient inputs challenge the health and functioning of aquatic ecosystems. To improve riverine water quality management, it is necessary to understand the underlying biogeochemical and physical processes, anthropogenic drivers and their interactions at catchment scale. We hypothesize that the spatial heterogeneity of nutrient sources dominantly controls the variability of in‐stream concentration dynamics among catchments. We investigated controls of mean nitrate (NO3 − ), phosphate (PO4 3− ), and total organic carbon (TOC) concentrations and concentration‐discharge ( C‐Q ) relationships in 787 German catchments of a newly assembled data base, covering a wide range of physiographic and anthropogenic settings. We linked water quality metrics to catchment characteristics using partial least squares regressions and random forests. We found archetypal C‐Q patterns with enrichment dominating NO3 − and TOC, and dilution dominating PO4 3− export. Both the mean NO3 − concentrations and their variance among sites increased with agricultural land use. We argue that subsurface denitrification can buffer high nitrogen inputs and cause a decline in concentration with depth, resulting in chemodynamic, strongly positive C‐Q patterns. Mean PO4 3− concentrations were related to point sources, though the low predictive power suggests effects of unaccounted in‐stream processes. In contrast, high diffuse agricultural inputs explained observed positive PO4 3− C‐Q patterns. TOC levels were positively linked to the abundance of riparian wetlands, while hydrological descriptors were important for explaining TOC dynamics. Our study shows a strong modulation of anthropogenic inputs by natural controls for NO3 − and PO4 3− concentrations and dynamics, while for TOC only natural controls dominate observed patterns across Germany. Plain Language Summary: Phosphorus, nitrogen, and organic carbon are key elements of plants and all living organisms. Humans are altering the nutrient cycles especially, to improve agricultural productivity and through domestic and industrial wastewater. Excess nutrients in surface waters have harmed many aquatic ecosystems by causing toxic algal blooms and a loss of biodiversity. Low nutrient concentrations and habitat variability are similarly important to those ecosystems, but human interference with natural drivers is not yet fully understood. To better understand and disentangle natural or human controls, we investigated nutrient concentrations and their variability across German catchments with varying landscapes and anthropogenic conditions. The human impact is clearly visible for mean nitrate concentrations, while the (natural) subsurface properties mainly controlled the variability of riverine nitrate. In the past, phosphate inputs were usually linked to wastewater, yet we found the control of agricultural activities on concentration dynamics to be unexpectedly high. Organic carbon was mainly associated with natural sources related to riparian wetlands where interactions with other nutrients are possible. This understanding of dominant controls is important in order to adapt management strategies to ensure healthy aquatic ecosystems. Key Points: Riverine NO3 − dynamics are controlled by vertical concentration heterogeneity, which can result from subsurface denitrification Diffuse P sources exert a strong control on the spatial variability of PO4 3− export patterns in contrast to point sources Share of riparian wetlands controls the mean TOC concentrations in German catchments